What happened to the body of Julia Pastrana (1834-1860)? Addressing ethical issues and human remains - Márquez-Grant, Nicholas (Elsevier, 2020)
In July 1857, the journal The Lancet published a note by Laurence [1] on a bearded and hairy lady who was visiting London that year as part of a show in Regent Gallery. Her name was Julia Pastrana.